2022
DOI: 10.1111/bjd.21834
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox: a new differential diagnosis when addressing genital ulcer disease

Abstract: We describe a case of genital ulcer and inguinal adenopathies that were attributable to monkeypox virus infection. We suggest clinicians adopt a low threshold for suspicion, particularly when evaluating genital ulcer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 4 publications
1
12
0
1
Order By: Relevance
“…122 And genital rashes were observed in many cases, which was also recently proven in another studies. [264][265][266][267][268][269][270] Other recent reports describe similar clinical characteristics. 180,271,272 Patel and colleagues 272 demonstrated that all 197 monkeypox infection cases developed mucocutaneous lesions, typically in the genitals (111 of 197 patients) or the perianal areas, causing rectal pain and penile edema.…”
Section: Clinical Characteristicssupporting
confidence: 61%
“…122 And genital rashes were observed in many cases, which was also recently proven in another studies. [264][265][266][267][268][269][270] Other recent reports describe similar clinical characteristics. 180,271,272 Patel and colleagues 272 demonstrated that all 197 monkeypox infection cases developed mucocutaneous lesions, typically in the genitals (111 of 197 patients) or the perianal areas, causing rectal pain and penile edema.…”
Section: Clinical Characteristicssupporting
confidence: 61%
“…The public, healthcare professionals, and government should be vigilant and promote preventive measures and appropriate diagnostic testing. By including mpox in the differential diagnosis of (1) papulovesicular or vesiculopustular lesions and (2) genital lesions/ulcers, dermatologists may play an essential role in the timely diagnosis and treatment of new cases, thereby preventing the spread of the disease [7,23].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, 67% experienced fatigue, 57% reported fever, and 18% did not present with any prodromal symptoms [22]. In some instances, the genital ulcers were painless with bilateral inguinal lymphadenopathy, mimicking primary syphilis [23].…”
Section: Anogenital Skin Lesions Are a Dominant Symptom In The 2022 O...mentioning
confidence: 99%
“…Clinical symptoms in each of these cases ( Figure 5 ) vary, but fever, weight loss, nasal discharge, coughing, respiratory involvement, and mouth ulcers may establish [ 2 , 47 , 54 ]. MSM have been reported to represent the majority of cases in the current outbreak, often resulting in genital lesions or a vesicular–pustular rash [ 40 , 55 , 56 , 57 , 58 , 59 ]. The fact that the perineum and vaginal area are commonly affected by the rash suggests that sexual contact may have been the cause of the condition.…”
Section: Symptomsmentioning
confidence: 99%